Ecosystem services of reed and seagrass debris on a urban Mediterranean beach (Poetto, Italy). (5th July 2022) - Ruju, Andrea; Buosi, Carla; Coco, Giovanni; Porta, Marco; Trogu, Daniele; Ibba, Angelo; De Muro, Sandro
Abstract: This paper reports a scientific inquiry carried out within the management process of an exceptional accumulation of reeds and seagrasses that took place in December 2019 on Poetto beach (Cagliari, southern Sardinia, western Mediterranean). The magnitude of the event raised concern within the local community and tourism service providers especially for the compromised beach accessibility caused by this large amount of biomass. The scientific inquiry is carried out in support of coastal management, to assess the berm processes before the removal of the reed wracks decided by the local municipality. By means of a numerical approach, this work devotes special attention to the runup induced by storms in the presence of reed and seagrass deposits on a low-lying backshore. Field surveys reported relatively large conductivity parameters in the presence on reed and seagrass deposits. The numerical approach shows that the increased beach permeability can eventually mitigate coastal flooding induced by storms. These results highlight the ecosystem services provided by reed and seagrass wracks together with the implications for coastal protection and management. Highlights: Large permeability values were measured in areas with seagrass and reed deposits. A numerical approach assesses runup and infiltration processes on a sandy beach. Reed and seagrass wracks can mitigate flooding by increasing beach permeability.